A Pilot Study of the Effects of Swimming Goggles on Meibomian Glands. Issue 4 (April 2022) - Thomas De Jesus, Melinda; Paugh, Jerry R.; van de Pol, Corina; Sasai, Alan; Ridder, William R.; Nguyen, Andrew Loc
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: This study evaluated whether swimming goggle wear contributes to meibomian gland (MG) atrophy or functional change. Methods: Subjects included minimal goggle wear experience (normal subjects) and maximal goggle wear experience (competitive swimmers). Principal outcome measures were meiboscore and percent MG area remaining percent gland area remaining [PGAR]). Clinical tests included symptoms, tear meniscus height, lipid layer thickness, fluorescein tear breakup time, corneal and conjunctival staining, lower lid margin signs, gland secretion quality, Schirmer I, and meibography. Results: Forty-two age-matched, and sex-matched subjects completed the study (25 normal subjects and 17 goggle-wearing swimmers). Tear breakup time was significantly shorter in goggle wearers ( P =0.016, Mann–Whitney U ). Differences in meibography, symptoms, and other clinical dry eye workup parameters were not statistically significant (all P values >0.05). Regression analysis indicated that sex, tear breakup time, and meiboscore statistically impacted PGAR. Conclusions: There was no apparent difference in MG morphology and function between goggle-wearing swimmers and nongoggle-wearing control subjects in this study sample. Although swimming goggles have been documented as having adverse effects on the periorbital tissues, mechanical forces from long-term swimming goggle wear may not impact MG morphology or function. The tarsal plate likely plays a protective role for the MGs from external mechanical friction from swimming goggles.